THE INFLUENCE OF CREATIVE AND INNOVATIVE WORK CULTURE ON ALYA TANI'S ENTREPRENEURSHIP - Eman Sulaeman; Alya Abidatul Maula; Delis Kartikawati; Eva Amalia Nuralifah (Universitas Islam Lamongan, 2023)
The purpose of this study was to analyze the influence of a creative and innovative work culture on Alya Tani's entrepreneurship. The research method used is a qualitative research method using interviews and literature. In qualitative research methods, researchers interview respondents to get information directly from them. Besides that, the researcher also used the library method to collect information about the research topic from the literature. From the results of the analysis, it was found that the Alya Tani agricultural medicine kiosk is a place that provides safe and quality agricultural medicinal products, and its employees have high creativity so as to provide consulting services that are successful in solving customer plant pest problems. They also focus on maintaining product quality and services that satisfy consumers.